AKUNTANSI PERSEDIAAN PADA SOFTWARE ACCURATE BAGI PELAJAR GEN-Z - Sastrasasmita, Emillia; Lie, Angel; Niandra, Ratna (Jurnal Serina Abdimas, 2024)
The Community Service (PKM) implementation team from the Faculty of Economics and Business, Tarumanagara University found that students in high school today are a generation that is familiar with the internet and information technology. Ease of accessing information is a daily part of the lives of students who are often referred to as GEN-Z . The traditional learning process that uses textbooks and lecture models in class is not effective for GEN-Z because it is considered uninteresting and boring. Based on the differences in character of GEN-Z , the current teaching and learning process needs to be adjusted to suitable learning methods and styles. However, the application of technology has two opposing sides, namely on the one hand technology can provide positive benefits such as time efficiency but on the other hand can result in failure due to the unpreparedness of its users. The development of technology in accounting requires adaptation and a continuous learning process from companies, accountants, accounting students and students who study accounting lessons at school. Accurate Software is one of the applications of information technology-based accounting that introduces accounting through computers to GEN-Z students at the high school level. PKM partners are students of SMA Kristen Yusuf located in West Jakarta. The PKM implementation method is through discussing inventory modules that are worked on directly on laptops at school. The output produced is in the form of participation in SENAPENMAS which is held periodically by Tarumanagara University and copyright on HKI. ABSTRAK Tim pelaksana Pengabdian Kepada Masyarakat (PKM) dari Fakultas Ekonomi Bisnis Universitas Tarumanagara mendapati bahwa para pelajar yang berada di bangku SMA saat ini adalah generasi yang akrab dengan internet dan teknologi informasi. Kemudahan dalam mengakses informasi adalah bagian keseharian dari kehidupan para pelajar yang sering disebut sebagai GEN-Z . Proses pembelajaran tradisional yang menggunakan buku cetak serta model ceramah di kelas tidak efektif bagi GEN-Z karena dianggap tidak menarik dan membosankan. Berdasarkan perbedaan karakter dari GEN-Z , maka proses belajar mengajar saat ini perlu disesuaikan dengan metode dan gaya pembelajaran yang cocok. Namun penerapan teknologi memiliki dua sisi yang bertolak belakang, yaitu di satu sisi teknologi dapat memberikan manfaat yang positif seperti efisiensi waktu namun di lain sisi dapat mengakibatkan kegagalan akibat ketidaksiapan penggunanya. Perkembangan teknologi pada akuntansi membutuhkan adaptasi dan proses pembelajaran berkelanjutan dari para pihak perusahaan, akuntan, mahasiswa akuntansi maupun pelajar yang mempelajari pelajaran akuntansi di sekolah. Software Accurate adalah salah satu penerapan akuntansi berbasis teknologi informasi yang mengenalkan akuntansi melalui komputer kepada pelajar GEN-Z di jenjang SMA. Mitra PKM adalah para pelajar SMA Kristen Yusuf yang berlokasi di Jakarta Barat. Metode pelaksanaan PKM adalah melalui pembahasan modul persediaan yang dikerjakan langsung pada laptop di sekolah. Luaran yang dihasilkan berupa keikutsertaan pada SENAPENMAS yang diadakan berkala oleh pihak Universitas Tarumanagara dan hak cipta pada HKI.